2008
DOI: 10.1261/rna.952208
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct structural elements of 5S rRNA are needed for its import into human mitochondria

Abstract: RNA import into mitochondria is a widespread phenomenon. Studied in details for yeast, protists, and plants, it still awaits thorough investigation for human cells, in which the nuclear DNA-encoded 5S rRNA is imported. Only the general requirements for this pathway have been described, whereas specific protein factors needed for 5S rRNA delivery into mitochondria and its structural determinants of import remain unknown. In this study, a systematic analysis of the possible role of human 5S rRNA structural eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 56 publications
1
79
0
2
Order By: Relevance
“…Two days after transfection, mitochondria were isolated and purified as described (Entelis et al 2001), and total and mitochondrial tRNAs were resolved in denaturing gels and analyzed by Northern hybridization with 59-32 P-labeled oligonucleotide probes against the 39-part of yeast tRNA CUU Lys (for tRK1 and small synthetic RNAs detection), human cytosolic tRNA Lys (to check possible cytosolic contamination in mtRNA preparation), and human mitochondrial tRNA Thr (Table 6). The import efficiency of RNAs was then estimated after quantification in a Typhoon-Trio scanner as a ratio between the signal obtained after hybridization with an anti-tRK1 probe and that obtained after hybridization with an oligonucleotide against the mitochondrial tRNA Thr in the mitochondrial RNA preparation, as described previously (Smirnov et al 2008). In order to compare import efficiencies of different RNAs, the total level of each RNA in transfected cells should be taken into account and normalized.…”
Section: Rna Import In Vivomentioning
confidence: 99%
“…Two days after transfection, mitochondria were isolated and purified as described (Entelis et al 2001), and total and mitochondrial tRNAs were resolved in denaturing gels and analyzed by Northern hybridization with 59-32 P-labeled oligonucleotide probes against the 39-part of yeast tRNA CUU Lys (for tRK1 and small synthetic RNAs detection), human cytosolic tRNA Lys (to check possible cytosolic contamination in mtRNA preparation), and human mitochondrial tRNA Thr (Table 6). The import efficiency of RNAs was then estimated after quantification in a Typhoon-Trio scanner as a ratio between the signal obtained after hybridization with an anti-tRK1 probe and that obtained after hybridization with an oligonucleotide against the mitochondrial tRNA Thr in the mitochondrial RNA preparation, as described previously (Smirnov et al 2008). In order to compare import efficiencies of different RNAs, the total level of each RNA in transfected cells should be taken into account and normalized.…”
Section: Rna Import In Vivomentioning
confidence: 99%
“…In our previous study, we identified structural elements of 5S rRNA serving as signals of its mitochondrial import, localized in the proximal part of helix I and in the loop D-helix IV region ( Fig. 1A; Smirnov et al 2008a). It had also been hypothesized that these regions correspond to binding sites with protein factors recruited to transport the RNA to the organelles.…”
mentioning
confidence: 94%
“…We show that human mitochondrial ribosomal protein L-18 (MRP-L18), a homolog of the Escherichia coli large ribosomal subunit protein L18, a member of a protein family L18/eL5 embracing the most conserved 5S rRNA-binding ribosomal proteins (Ban et The secondary structure of human 5S rRNA and its main functional sites (Smirnov et al 2008a(Smirnov et al ,b, 2010. ( , or containing deletion in the g-domain (as indicated below the panels).…”
mentioning
confidence: 99%
“…In addition to in vitro evidence for a protein-only RNase P enzyme within mitochondria (9), the nucleus-encoded RNA components of RNase P and MRP enzymes are also imported into mitochondria and function in mitochondrial (mt)DNA replication and transcription (10)(11)(12). The 5S ribosomal RNA translocates into mitochondria, assembles with ribosomes (13,14), and may function in mtRNA translation, although the exact function of the 5S ribosomal RNA within mitochondria has yet to be firmly established. Finally, specific nucleus-encoded microRNAs have been isolated from mitochondria (7,15).…”
mentioning
confidence: 99%